ICG angiography predicts burn scarring within 48 h of injury in a porcine vertical progression burn model. Issue 5 (August 2015) - Fourman, Mitchell S.; McKenna, Peter; Phillips, Brett T.; Crawford, Laurie; Romanelli, Filippo; Lin, Fubao; McClain, Steve A.; Khan, Sami U.; Dagum, Alexander B.; Singer, Adam J.; Clark, Richard A.F.
Highlights: We compare indocyanine green and laser Doppler in the prediction of burn scarring. We utilized a validated vertical progression porcine burn model. Indocyanine green fluorescence predicted burn contraction within 2 days of injury. Laser Doppler failed to show significant predictive potential. Human studies necessary to discern full utility of ICG angiography in burns. Abstract: The current standard of care in determining the need to excise and graft a burn remains with the burn surgeon, whose clinical judgment is often variable. Prior work suggests that minimally invasive perfusion technologies are useful in burn prognostication. Here we test the predictive capabilities of Laser Doppler Imaging (LDI) and indocyanine green dye (ICG) angiography in the prediction of burn scarring 28 days after injury using a previously validated porcine burn model that shows vertical progression injury. Twelve female Yorkshire swine were burned using a 2.5 × 2.5 cm metal bar at variable temperature and application times to create distinct burn depths. Six animals (48 injuries total) each were analyzed with LDI or ICG angiography at 1, 24, 48, and 72 h following injury. A linear regression was then performed correlating perfusion measurements against wound contraction at 28 days after injury. ICG angiography showed a peak linear correlate ( r 2 ) of .63 (95% CI .34 to .92) at 48 h after burn. This was significantly different from the LDI linear regression ( p  < .05), which was measured at r 2 of .20 (95% CI .02 to .39). ICG angiography linear regression was superior to LDI at all timepoints. Findings suggest that ICG angiography may have significant potential in the prediction of long-term burn outcomes.